The Role of Parents in Learning Guidance Post Covid-19 Pandemic - Latifah, Latifah; Pernama, Ayu; Prihandani, Tia (Grief and Trauma, 2024)
The urgency of this research lies in the critical need to understand and enhance the role of parents in supporting children's education in the post-COVID-19 pandemic era. The pandemic has drastically transformed the learning environment, shifting much of the teaching and learning process to an online format. This sudden transition has left many children feeling overwhelmed, confused, and often bored. Recognizing parents as the primary figures responsible for their children's education at home, this study aims to determine how effectively parents’ guide their children through the learning process in this new educational landscape. Utilizing a qualitative research approach, this study employs observation, documentation, and interview techniques to collect both primary and secondary data. Primary data are gathered through interviews, while secondary data are sourced from relevant journals, books, and archives. The findings highlight the pivotal role parents play in motivating and directing their children's learning, emphasizing the need for targeted support and resources to empower parents in this role.